University student wellbeing during COVID-19: associations with infection prevalence and social gathering restrictions in an observational study - Noble, Donald J.; Raison, Charles L. (Frontiers in Psychiatry, 2026)
BackgroundThe COVID-19 pandemic served as a global, uncontrolled social isolation experiment, with especially pernicious effects on the wellbeing of young adults. We sought to understand how the COVID-19 pandemic impacted the wellbeing of university undergraduate students, distinguishing between factors related to infection prevalence and those linked to social restriction.Methods277 total U.S. undergraduate students enrolled in a course on mental wellbeing and resilience that was offered once each year from 2020 to 2024. Students anonymously completed surveys assessing anxiety, depression, and subjective wellbeing on a weekly basis. These behavioral data were aggregated and investigated for associations with local COVID-19 case levels and a university social gathering meter.ResultsSubjective wellbeing declined a few months into the COVID-19 pandemic in Fall 2020, remaining low in Fall 2021 and Spring 2022, with 63.7% of students at-risk for poor wellbeing over these three semesters based on the standard cutoff. Depression and anxiety peaked during Fall 2021 with 39.0% and 34.5% of students at-risk for anxiety and depressive disorders, respectively. Wellbeing gradually improved following the return to in-person learning in mid-Spring 2022. Over all five semesters, survey questions reflecting anhedonia associated with social gathering restrictions whereas questions assessing acute anxiety associated with local COVID-19 case levels.ConclusionsOur findings highlight the negative impact of the COVID-19 pandemic on university student wellbeing and suggest that COVID-19 infection prevalence and associated social isolation measures may have uniquely influenced different aspects of wellbeing. More research is needed to assess causality, while accounting for other potential socio-economic and academic factors.